(untitled) (Nuntius Antiquus, 2014)
This article deals with procedures for expressive translation of Seneca’s tragedies, Oedipus and Phoenissae. The research is part of a project of study on expressiveness in such tragedies, defining the stylistic idiom used by the author in both plays, so that those expressiveness’ marks from source texts can be valued and transferred into target texts. Thus, besides the translation project itself, the expressive effects on a small part of Phoenissae (654-659) are presented and, finally, the verses are translated into Brazilian Portuguese.